151. The Use of Dried Blood Spot Cards to Assess Serologic Responses of Individuals Vaccinated Against Measles, Hepatitis A, Tetanus, Influenza and Varicella Zoster. (31st December 2020) - Danko, Janine R; Taylor, Robert; Reinhardt, Brian; Watson, Nora L; Banks, Taylor
Abstract: Background: Traditional blood sampling by venipuncture is cumbersome and expensive. Dried Blood Spot (DBS) sampling is desirable because of its ease of sample collection, transportation and storage. It has been used in clinical diagnosis but not been thoroughly studied for the potential use to assess the immune status of individuals following natural infection or preventive vaccination. The goal of this study is to compare DBS to traditional blood samplings in detection of antibodies in individuals vaccinated against measles, hepatitis A, tetanus, influenza and varicella zoster. Methods: Blood from 220 vaccinated individuals were collected by venipuncture into serum separation tubes and by fingerstick onto Whatman 903® protein saver cards. ELISA was used to test DBS eluates and serum samples for antibodies against measles, varicella, tetanus and hepatitis A. Sensitivities, specificities, and correlation coefficients were evaluated to compare optical density (OD) values of paired serum and DBS samples. Hemagglutinin inhibition (HAI) and microneutralization assay (MNA) were used to determine anti-influenza antibody in serum and DBS samples. The long term stability of DBS samples at different temperatures was assessed using simulated immune measles blood. Results: DBS OD was highly correlated with serum OD for antibodies to measles (r = 0.93), varicella (r = 0.82), and tetanus (r = 0.91) (Fig.1). Sensitivities of DBS OD ranged from 86–99% and specificities ranged from 96–100% using cut-offs established by each assay. By contrast, the hepatitis A data showed a low sensitivity (31%) and a weak correlation (r = 0.14) between DBS and serum samples. HAI and MNA assays showed a broad range of anti-influenza A (H1N1 and H3N1) antibody titers in serum samples but failed to detect the antibodies in DBS eluates. The stability data indicated that DBS samples were stable for 4 weeks when stored at room temperature and for 6 months at 4°C (Fig. 2). Figure 1. Correlation of antibody levels detected by DBS sampling to the antibody levels detected by serum sampling for measles, hepatitis A, tetanus and varicella zoster. Figure 2. Stability of the blood samples on DBS cards stored under various temperatures for 25 weeks as measured by the titers of anti-measles antibody (IgG) at various time points. Conclusion: DBS sampling was sensitive, specific, and highly correlated with traditional venipuncture sampling in detection of antibodies against measles, tetanus and varicella zoster, but not hepatitis A and influenza. Thus, the success of using DBS sampling to assess the antibody levels in immunized individuals may be dependent on the pathogens and the type of assay used. Disclosures: All Authors : No reported disclosures